First evidence of a mid-Holocene earthquake-triggered megaturbidite south of the Chile Triple Junction - Piret, Loic; Bertrand, Sebastien; Kissel, Catherine; De Pol Holz, Ricardo Hernán; Tamayo Hernando, Alvaro; Van Daele, Maarten (My University, 2018)
Megaturbidites have been the focus of many paleoseismic and paleoenvironmental studies because they can provide evidence for catastrophic and/or hazardous events with potentially major environmental implications. During a recent research cruise in Baker Fjord, Chile (47 degrees 54 ' S-74 degrees 30 ' W), a megaturbidite was described between the Northern and Southern Patagonian Icefields. Here, we aim to determine the depositional processes of the megaturbidite and identify its origin. Based on the turbidite's location, a possible origin was the early Holocene drainage of paleo-lake General Carrera, which was recently proposed in the literature as having produced a Glacial Lake Outburst Flood (GLOF) that drained through Baker Fjord. Due to the fjord's location in a subduction zone, and close to the Chile Triple Junction, however, seismic activity must also be considered as a potential triggering mechanism. To achieve our goals, we undertook a multi-proxy analysis of sediment core MD07-3121, including sedimentology (grain size, loss-on-ignition, foraminifera counts), magnetic properties, bulk organic geochemistry, and radiocarbon dating, and we analysed bathymetric maps and sub-bottom profiles. Our grain-size results display a diagnostic fining upward trend and show evidence of seiching in the 733-cm-thick megaturbidite. The age of the event (5513-5211 cal yr BP) contradicts the hypothesis of an early Holocene GLOF origin. Bulk organic geochemical results indicate that the sediments that compose the turbidite are clearly of marine origin, which further goes against a GLOF origin. In addition, the megaturbidite is underlain by a 1136 cm thick mass transport deposit (MTD), also composed of marine sediments. According to the sub-bottom profiles, the MTD and the megaturbidite originate from the reworking of thick packages of sediment previously deposited on nearby sills and on the fjord's flanks. Furthermore, similar coeval deposits are found in an adjacent sub-basin. We therefore interpret these deposits to be triggered by an earthquake during the late mid-Holocene. While megathrust and intraslab earthquakes are possible in the region, we argue that a crustal earthquake is the most likely seismic trigger in the study area. This study reveals the first earthquake-triggered megaturbidite south of the Chile Triple Junction. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: turbidite; sediment provenance; patagonia; holocene; earthquake